Wavelet image compression by using hybrid kernel SVM - Jia-Ming Chen; Lei Li; Ling-Ye Nie (2008 International Conference on Machine Learning and Cybernetics, 2008)
In this paper, we proposed a way through combining the support vector machines (SVM) with hybrid kernel and wavelet transform to compress the image. SVM regression could learn dependency from training data and realized compression by using fewer training point (support vectors) to represent the original data and eliminate the redundancy. Wavelet coefficients could be compressed based on this feature. Further more, the hybrid kernel applied can enhance the compress efficient and improve the picture quality by controlling the VC-dimension (Tan, 2004) of SVM. At last, we use the arithmetic coding to encode the dates from the output of the SVM and finish the image compression.